The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/rs12060932
|View full text |Cite
|
Sign up to set email alerts
|

A Mapping Review on Urban Landscape Factors of Dengue Retrieved from Earth Observation Data, GIS Techniques, and Survey Questionnaires

Abstract: To date, there is no effective treatment to cure dengue fever, a mosquito-borne disease which has a major impact on human populations in tropical and sub-tropical regions. Although the characteristics of dengue infection are well known, factors associated with landscape are highly scale dependent in time and space, and therefore difficult to monitor. We propose here a mapping review based on 78 articles that study the relationships between landscape factors and urban dengue cases considering household, neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 206 publications
3
20
0
2
Order By: Relevance
“…Despite this interest, Guo et al (2017) identified only around 20 articles between 1990 and 2015 that addressed the spatial components of dengue fever outbreaks [ 34 ]. Marti et al (2020) reviewed the literature and created an inventory of the most relevant landscape factors for dengue transfer in urban areas [ 35 ]. They identified 78 articles that met quality and content criteria and then structured their review according to geographic context, epidemiological descriptors, landscape factors, and evidence of a relationship between urban determinants and dengue cases [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this interest, Guo et al (2017) identified only around 20 articles between 1990 and 2015 that addressed the spatial components of dengue fever outbreaks [ 34 ]. Marti et al (2020) reviewed the literature and created an inventory of the most relevant landscape factors for dengue transfer in urban areas [ 35 ]. They identified 78 articles that met quality and content criteria and then structured their review according to geographic context, epidemiological descriptors, landscape factors, and evidence of a relationship between urban determinants and dengue cases [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Marti et al (2020) reviewed the literature and created an inventory of the most relevant landscape factors for dengue transfer in urban areas [ 35 ]. They identified 78 articles that met quality and content criteria and then structured their review according to geographic context, epidemiological descriptors, landscape factors, and evidence of a relationship between urban determinants and dengue cases [ 35 ]. This study emphasized the need to consider multiple variables, given the complexity of the ‘pathogenic landscape’ and to find ways of using remote sensing to describe intricate urban environments, minimizing the need for costly and time-consuming surveys [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sallam et al [8] proposed a systematic review that summarized land cover, meteorological and socioeconomic factors of Aedes habitats, referring to dengue vectors. Moreover, our previous mapping review [9] focused on the dengue transmission in urban landscapes, and urban landscape factors derived from satellite EO data, Geographic Information System (GIS) techniques and survey questionnaires; spatial scales and dengue-landscape relationships were identified from 78 relevant studies published from inception to 31 December 2019. Despite all this, there is still a lack of overview on satellite EO data and landscape factors that could be of benefit to science and society by guiding future studies of disease risk prediction and improving health decision-making at different spatial scales (e.g., from global to local).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite Earth observation sensors and derived products used for identifying dengue landscape factors. Information on spatial and temporal resolution was taken from Huete et al[27], Hamm et al[26] and Marti et al[9].…”
mentioning
confidence: 99%